AB0987 Unexpected Balance Skills of Patients with Polyarticular Juvenile Idiopathic Arthritis Before and After 10 Months of Anti-TNF-α Therapy Compared to Healthy Controls. (9th June 2015) - Merker, J.; Hartmann, M.; Kreuzpointner, F.; Schwirtz, A.; Haas, J.-P.
Abstract : Background: Patients with polyarticular Juvenile Idiopathic Arthritis (JIA) suffer from functional impairments caused by inflammation [1]. While medical treatment leads to an improvement of disease activity in JIA [2], little is known about the effects on conditional or on coordinative abilities. Both are very important in daily living. Objectives: The aim of this work is to verify the balance control of JIA patients before and after 9.8 (Q25: 8.5/Q75: 11.3) months with initial adjustment to an anti-TNF-α therapy combined with functional treatment (e.g. physiotherapy) in comparison to healthy peers. Methods: Longitudinal effects on balance control of twenty-six patients with polyarticular JIA were analysed before (T0) and after ten months (T1) with an anti-TNF-α therapy combined with functional treatment (median for duration of disease: T0 6.8yr). In addition, a healthy age matched control group (CG; n=26) was included in the study. The balance control was measured with the S3-Check (TST, Großhoeflein). This is a validated measurement system for functional evaluation of stability and sensorimotor ability of the body [3]. The board has one axis of rotation, which enables an alternation up to an overturning of 12° from left to right. The subjects stand barefoot on the S3-Check with an arbitrary arm position. They had the announcement to keep the board for 30 seconds as horizontal as possible. The best results of the stability and sensory indices after three trials were compared with the Wilcoxon signed-rank and Mann-Whitney-U test (p<0.05). Results: JIA patients had significantly lower stability and sensory indices compared to the healthy peers. The balance indices of the patients did not differ between T0 and T1. In anthropometric characteristics no significant differences could be found between the patients and controls. All results are presented in table 1 . Conclusions: Lower balance indices of the S3-Check demonstrate that the JIA patients had a significantly better stability and motor control than controls. The patients are able to react better to variable positions of the balance board. As all JIA patients included suffered from bad controlled polyarticular JIA, daily compensatory movements in consequence of polyarticular joint pain might have a positive effect on balance control. Additionally an increased body-awareness of patients by long-term functional physiotherapy could further amplify this effect. An anti-TNF-α therapy of ten months did not further improve coordinative ability. The positive results emphasize the significance of functional treatment in polyarticular JIA patients. References: Hartmann M et al. (2010). Int J Pediatrics Vol 2010. Minden K et al. (2013). Z Rheumatol 72(4): 339-46. Raschner C et al. (2008). Sportverl Sportschad 22:100-5. Acknowledgements: The authors want to thank Pfizer Inc., the "Deutsche Kinderrheuma-Stiftung" and "Ironman-Hilfe Kinderrheuma" for supporting this study. Disclosure of Interest: None declared